Comparative Analysis of the Notes to the Financial Statement of Companies Engaged in Sports Activities in Hungary, Based on the Information of the General Part - Kerezsi, Dóra; Bács, Zoltán; Böcskei, Elvira; Zéman, Zoltán; Tarnóczi, Tibor; Fenyves, Veronika (International Journal of Engineering and Management Sciences, 2019)
Contribution of the sports sector to GDP in the EU Member States is close to 5%, while in Hungary it is approximately 1-1.5%. This ratio is likely to increase, for which various subsidies of corporate tax provide a good basis. The information mentioned above confirms that the economic analysis of companies engaged in sports activities is an interesting and necessary field of research. In our research, we examine whether the notes on the accounts of companies include the information, which could help obtain necessary financial knowledge concerning the partner companies. For the analyses, we used the notes on the accounts of companies, which have sports activity (Hungarian NACE No. 931) as their main line of business. By means of text mining, we analyse the extent to which the notes on the accounts are in conformity with the Accounting Act. The sports activity companies are analysed using various packages of the R statistical system. By means of text mining, we analyse the extent to which the notes on the accounts provide the necessary information that would be indispensable for the proper interpretation of the balance sheet and the profit and loss account.